2016
DOI: 10.1371/journal.pone.0164928
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Cross-Validation of the ActiGraph wGT3X+ Accelerometer for the Estimation of Physical Activity Intensity in Children with Intellectual Disabilities

Abstract: BackgroundValid objective measurement is integral to increasing our understanding of physical activity and sedentary behaviours. However, no population-specific cut points have been calibrated for children with intellectual disabilities. Therefore, this study aimed to calibrate and cross-validate the first population-specific accelerometer intensity cut points for children with intellectual disabilities.MethodsFifty children with intellectual disabilities were randomly assigned to the calibration (n = 36; boys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…This is a standard cut point based on research in the general population and may not be valid for adults with intellectual disabilities. Adults with intellectual disabilities have shown to fidget more whilst sedentary (Ohwada, Nakayama, Suzuki, Yokoyama, & Ishimar, ) and may require a higher cut point to classify sedentary behaviour, as shown to be required in children with intellectual disabilities (McGarty, Penpraze, & Melville, ). Therefore, there is a need for more focussed measurement research in adults with intellectual disabilities to investigate the validity of accelerometer‐based devices to measure sedentary time and the validity of existing cut points.…”
Section: Discussionmentioning
confidence: 99%
“…This is a standard cut point based on research in the general population and may not be valid for adults with intellectual disabilities. Adults with intellectual disabilities have shown to fidget more whilst sedentary (Ohwada, Nakayama, Suzuki, Yokoyama, & Ishimar, ) and may require a higher cut point to classify sedentary behaviour, as shown to be required in children with intellectual disabilities (McGarty, Penpraze, & Melville, ). Therefore, there is a need for more focussed measurement research in adults with intellectual disabilities to investigate the validity of accelerometer‐based devices to measure sedentary time and the validity of existing cut points.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that a recent systematic review of the moderate-to-vigorous physical activity (MVPA) content of school PE globally suggested that a minority of time in PE classes was spent in MVPA. 14 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, valid and reliable methods, which are population‐specific and sensitive to change, are essential to test the effect of interventions (McGarty et al . ).…”
Section: Discussionmentioning
confidence: 97%